Analisis Pendapatan dan Strategi Pemasaran Petani Mangga Gadung di Desa Bandilan Kecamatan Prajekan Kabupaten Bondowoso - Zul Amal, Ikhlas; Aden Hawa, Tidar; Nisa’, Khoirotun (Program Studi Agribisnis, 2024)
Mango is one of the commodities that is widely favored by most people in Indonesia and is easy to cultivate. The purpose of this research is to determine the income of the Mangga Gadung farming business, to understand the marketing mix of the Mangga Gadung farming business, and to identify the strategies of the Mangga Gadung farming business in Bandilan Village, Prajekan District, Bondowoso Regency. The sampling method used is Purposive Sampling. The results of this study indicate that the income from mango farming in the Kutilang Jaya 5 farmer group in Bandilan village amounted to Rp 61,950,000, with total fixed and variable costs of Rp 36,577,903, resulting in a net income of Rp 25,207,597 from mango farming in the Kutilang Jaya 5 farmer group in Bandilan village. Next, the marketing mix of mangoes in the Kutilang Jaya 5 farmer group in Bandilan Village, after being analyzed using the 7P framework, needs to further develop promotion, one of the promotional strategies being Edu-tourism. Finally, the SWOT analysis shows that the position of the SWOT matrix diagram is in quadrant I, which indicates an aggressive strategy with profitable results.